Importance of measuring endolysosome, cytosolic, and extracellular pH in understanding the pathogenesis of and possible treatments for glioblastoma multiforme - Halcrow, Peter W. (Cancer Rep (Hoboken), 2019)
BACKGROUND: Glioblastoma multiforme (GBM) is a very aggressive form of brain cancer that carries with it a tragically poor prognosis. As with many other forms of cancer, the extracellular environment near GBM tumors is acidified and is relevant to the pathogenesis of GBM because decreased pH promotes tumor cell invasion, increases angiogenesis, decreases immune surveillance, and increases resistance to possible treatments. Recently, vacuolar ATPase (v‐ATPase), a proton pump that helps maintain the acidic environment in endosomes and lysosomes (hereafter referred to endolysosomes) as well as proton gradients across the plasma membrane, was identified as a novel therapeutic target for GBM. However, information is lacking about cancer cell and tissue pH of endolysosomes, cytosol, and extracellular fluid. AIMS: Here, we measured endolysosome, cytosolic, and extracellular pH in U87MG cells in the absence and presence of the v‐ATPase inhibitor bafilomycin A1. METHODS: In vitro measurements of U87MG cells were conducted using LysoSensor dye and a Lysosome‐RFP dye for lysosome pH, BCECF‐AM for cytosolic pH, and a pH‐sensitive microprobe for extracellular pH. RESULTS: Bafilomycin A1 increased endolysosome pH from 5.28 to 5.57, decreased cytosolic pH from 7.01 to 6.46, and increased extracellular pH from 7.18 to 7.40. CONCLUSIONS: Here, we report the ability to make pH measurements in U87MG glioblastoma cells and discuss these results in the context of GBM pathogenesis and possible treatment. This might be of some importance in understanding the pathogenesis of GBM because the highly regulated stores of hydrogen (H(+)) ions in endolysosomes can influence cytosolic and extracellular pH as well as the distribution, numbers, and sizes of endolysosomes.